PENGUATAN ETIKA KEHUMASAN MELALUI REORIENTASI HUMAS PADA LEMBAGA PENDIDIKAN ISLAM - Wahid, Abd Hamid; Hasanah, Istianatul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
This paper presents the strengthening of public relations ethics through the reorientation of public relations in Islamic educational institutions, where public relations has an important role in managerial activities in Islamic educational institutions. In its implementation, the role of public relations in Islamic educational institutions is still underestimated and lacks the right portion in its application. PR is only understood as a complementary administration in practice, thus causing educational institutions unable to manage good relations with the surrounding community as partners. This study uses a qualitative approach to the type of library research, where researchers want to clearly describe the object of study to be studied. Analysis of the data uses content analysis. The results of the study indicate that the reorientation of public relations in Islamic educational institutions must be based on; First, qaulan sadidan, Islamic educational institutions must convey factual and reliable information; Second, qaulan baligha, Islamic educational institutions communicate effectively, communicatively and easily understood; Third, qaulan ma’rufa, the communication process should avoid words that can offend partners / customers; Fourth, qoulan karima, public relations activities must respect partners, listen to aspirations and promote ethics; Fifth, Qaulan Layyina, public relations must be a friendship and friendship dissertation; Sixth, qaulan maysura, Islamic educational institutions must convey information that is easily understood and digested by the communicant.